Destination atmospheric cues as key influencers of tourists’ word-of-mouth communication: tourist visitation at two Mediterranean capital cities - Loureiro, S. M. C.; Stylos, N.; Bellou, V. (Tourism Recreation Research, 2021)
The impact of destination atmospheric cues–as representations of destination characteristics–on tourists’ intention to engage in word-of-mouth (WOM) communication is examined, adopting a well-established retailing theoretical underpinning; the Stimuli-Organism-Response (S-O-R) model. In doing so, this research incorporates both affective and cognitive states and processes as Organism. Evidence from 1025 tourists who visited Lisbon, Portugal and 1002 who visited Athens, Greece offers support to the S-O-R model and at the same time (a) exemplifies the explanatory power of Organism in the relationship between destination atmospheric cues and WOM communication intention, (b) recognizes the key role of negative affect for both destinations, as well as of the positive affect for Athens only, and (c) highlights the procedural nature of the cognitive state of Organism. This research corroborates the value of examining tourists’ behaviour through the lens of S-O-R and how both affective and cognitive elements of Organism contribute to decision-making in a procedural manner. Managerial implications for tourism destination marketers are also discussed.